The Cerro Azul Fisherman's Wharf, Peru: Revaluation and Tourism Promotion - WONG ORMEÑO, Kerby Gilberto; CUBA CARBAJAL, Nestor; CHENET ZUTA, Manuel Enrique; REYNOSA NAVARRO, Enaidy; YANGALI VICENTE, Judith Soledad (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
The Cerro Azul sinners dock, located in the Cerro Azul district, Cañete province in Lima, Peru, is a historical resource that is currently not valued. The objective of this study was to establish the potential relationship between the tourist appreciation of the fishing pier and the tourist promotion in the Cerro Azul-Cañete district. The research was of a non-experimental design, correlational descriptive level, with a quantitative approach. The questionnaire was applied as a data collection instrument. The sample consisted of 800 inhabitants of the Cerro Azul district, Cañete province in Lima, Peru. The results confirm the existence of a significant moderate correlation between the revaluation of the fishing pier and tourism promotion; accepting the alternative hypothesis, therefore, the reassessment of the resource with adequate tourist promotion would increase the tourist influx and the social, economic, and environmental development of the place.